Patients’ Mental Models and Adherence to Outpatient Physical Therapy Home Exercise Programs - Jon Rizzo; Alexandra Bell (Adult Education Research Conference, 2013)
Non-adherence to medical advice leads to costly physical and financial repercussions. Previous research suggests individuals’ mental models, comprising knowledge, beliefs, and prior experiences, may influence adherence behavior. This study explores these relationships by linking aspects of physical therapy patients’ mental models with their adherence to home exercise programs.